VARIATIONS OF PLASMA TEMPERATURES IN IONOSPHERE OVER KHARKIV IN THE SOLAR ACTIVITY GROWTH PHASE - Siusiuk, M. M.; Kotov, D. V.; Chernogor, L. F.; Bogomaz, O. V. (Видавничий дім «Академперіодика», 2016)
PACS numbers: 93.30.Ge, 94.20.Cf, 94.20.Dm, 94.20.Fg Purpose: presenting temperature variations of electrons and ions obtained at the Institute of Ionosphere (Kharkiv) with an incoherent scatter radar in the growth phase of the 24th cycleof solar activity, and compare them with the corresponding data of IRI-2012 model.Desing/methodology/approach: Data are obtained by incoherent scattering. Method of solving the inverse radiophysics problem was used for analysis. Two-dimensional ambiguity function was used for specification.Findings: A significant difference has been found between experimental data and model data. So, for all days of observation, the model overestimated the night temperature values and underestimated them by day. The maximum difference is about 500 K at night and 800 K in the daytime. Also, the effects of appearance of midday collapse of electron temperature during the equinoxes are considered.Conclusions: It is confirmed that to adequately describe the ionospheric processes it is necessary to use a systematic approachwhich takes into account, in particular, the interaction between ionospheric regions located in magneto-conjugate areas. Such regularities should be taken into account for correction of ionospheric model for the Central European region.Key words: incoherent scattering radar, electron temperature, ion temperature, midday collapse, morning and evening peaksManuscript submitted 05.10.2016Radio phys. radio astron. 2016, 21(4): 279-284 REFERENCES1. CHERNOGOR, L. F., 2006. Earth–atmosphere–ionosphere–magnetosphere as an open dynamic nonlinear physicalsystem (Part 1). Nelinejnyj mir. vol. 4, no. 12, pp. 655–697 (in Russian). 2. CHERNOGOR, L. F., 2007. Earth–atmosphere–ionosphere–magnetosphere as an open dynamic nonlinear physical system (Part 2). Nelinejnyj mir. vol. 5, no. 4, pp. 198–231 (in Russian). 3. EVANS, J. V., 1969. Theory and Practice of Ionospheric Study by Thomson Scatter Radar. Proc. IEEE. vol. 57, is. 4, pp. 496–530. DOI: https://doi.org/10.1109/PROC.1969.7005 4. SPACE WEATHER PREDICTION CENTER, 2016. F10.7 cm Radio Emission [online]. [viewed 27 August 2016]. Available from: http://www.swpc.noaa.gov/phenomena/f107-cm-radioemissions 5. SIUSIUK, M. N., KOTOV, D. V., CHERNOGOR, L. F. and BOGOMAZ, O. V., 2016. Variations of Plasma Temperatures in Ionosphere over Kharkiv During Extreme Solar Minimum. Radio Phys. Radio Astron. vol. 21, no. 2, pp. 132–140 (in Russian). DOI: https://doi.org/10.15407/rpra21.02.132 6. KRINBERG, I. A. and TASCHILIN A. V., 1984. Ionosphere and Plasmasphere. Moskow: Nauka Publ. (in Russian). 7. BANKS, P. M., 1969. The thermal structure of the ionosphere. Proc. IEEE. vol. 57, is. 3, pp. 258–281. DOI: https://doi.org/10.1109/PROC.1969.6959